ACL Force and Knee Kinematics After Posterior Tibial Slope-Reducing Osteotomy. Issue 7 (21st July 2017) - Yamaguchi, Kent T.; Cheung, Edward; Mathew, Justin; Boguszewski, Daniel V.; Markolf, Keith; McAllister, David R.; Petrigliano, Frank A.
Objectives: Although many patients have a good outcome after anterior cruciate ligament (ACL) reconstruction, a number of individuals will experience continued instability. There is evidence that the posterior tibial slope (PTS) of the tibial plateau may play a role in ACL injury. Theoretically, under tibiofemoral compression (TFC) a steeper PTS would induce greater anterior tibial translation, thus increasing ACL force. The objective of this study was to evaluate if a PTS-reducing osteotomy would reduce ACL force. Methods: Eleven fresh-frozen cadaveric knees were tested (mean age 27 years). The femoral attachment of the ACL was mechanically isolated and attached to a custom designed load cell to measure resultant ACL force. Using a six-degree-of-freedom robot, each knee was flexed from 0°-50° while maintaining 200N TFC combined with the following loading conditions: 45N anterior tibial force (AF), 5Nm valgus moment (VM), 2Nm internal tibial torque (IT), and all loads combined. After testing the normal knee, a 10° PTS-reducing osteotomy was performed. An anterior wedge of bone was removed distal to the plateau, which was then lowered and secured with external fixators. The knee was then re-tested. A paired t-test was used to analyze statistical significance between normal and osteotomized knees every 5° of flexion. Results: Osteotomy reduced PTS by 10.0° ± 0.2° (mean ± SD), resulting in a relative change in tibiofemoral position at full extension, in effect hyperextending the knee 9.4°±1.9° and shifting the tibia 7.9 ± 1.6 mm posteriorly, 3.2° ± 2.3° internally, and 3.2° ± 1.5° into valgus. Compared to the normal knee, the osteotomy significantly reduced resultant ACL force when loaded with 200N TFC + 45N AF and 200N TFC + 5Nm VM. However, ACL force was not reduced under 200N TFC + 2Nm IT or 200N TFC + all loading conditions combined (Figure 1). Conclusion: Our data shows in the absence of applied internal torque, the posterior tibial slope-reducing osteotomy altered knee kinematics which corresponded to a significant reduction in ACL force. However, this protective effect was lost when internal torque was applied.